Study of the kinetics of Cu and Hg adsorption from binary solutions using chitosan (Nexo Revista Científica, 2011)
In this work, the adsorption kinetic of Cu(II) and Hg(II) onto chitosan was studied from a binary solution at different initial concentration of metallic ions, at different particle sizes and agitation rate. Chitosan was obtained from shrimp shells. Solutions of 1 L of Cu(II) and Hg(II) were placed in contact with 2 g of chitosan and the mixture was agitated by 8 h. Afterwards, the samples were analysed by atomic absorption. The experimental data were tested by application of kinetic models of pseudo-first order and pseudo-second order. The results of adsorption process showed that in the most cases, both ions were effectively adsorbed by chitosan. The percentage of adsorption was 43-100 % and 94-100 % for Cu(II) and Hg(II), respectively. The results also showed that at low concentrations, experimental data were better adjusted by pseudo-first order models; meanwhile, at high concentration, the data were well described by the pseudo-second model. Therefore, the rate-limiting step is the adsorption reaction and not mass transfer. Keywords: Adsorption kinetics; Binary solution; Chitosan; Kinetic models; Shrimp shell DOI: http://dx.doi.org/10.5377/nexo.v24i1.591   Nexo, Vol. 24, No. 1, pp. 20-32, 2011